IDENTIFIKASI TELUR CACING ENDOPARASIT PADA FESES AYAM KAMPUNG (Gallus gallus domesticus) RUMPUT GANAS MINI FARM, LOA JANAN ILIR, SAMARINDA - Hasibuan, Febry Rahmadhani; Syahfitri, Widya; Br Hasibuan, Fitri Elizabeth Br Hasibuan; Ramadhani, Widiyanto; Ismail, Ahmad Yasin; Tsany, Alisha; Musdalifah, Yuni (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Parasites are divided into two based on their habitat, namely endoparasites and ectoparasites. Endoparasites are a group of parasites that live in the host's body to obtain food from the host. The spread of endoparasites in livestock can occur through contaminated feed, water, and livestock equipment. The purpose of this study was to identify the species of worm eggs in the feces of native chickens (Gallus gallus domesticus) at the Rumput Ganas Mini Farm, Loa Janan Ilir, Samarinda. 2g of chicken feces were taken and then 10 ml of NaCl solution was added. Homogenized and filtered using gauze. Poured into a centrifuge tube, then centrifuged for five minutes at a speed of 1500 rpm. The results of the centrifuge solution that settled on the surface were taken using a dropper pipette and then placed on an object glass. Covered using a cover glass, then observed under a microscope starting from the smallest magnification. The results of the study showed that two species of endoparasites were found in the feces of local chickens found in the mini farm loa janan ilir's vicious grass, namely Diphyllobothrium latum and Ascaridia galli. Keywords: Ascaridia galli, Dyphyllopbothrium latum, Endoparasite, Gallus gallus domesticus, Poultry Farming